2021
DOI: 10.1136/jitc-2021-003609
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally-driven myeloid NFkB and IFN/ISG responses predict malignancy risk, survival, and immunotherapy regime in ovarian cancer

Abstract: BackgroundTumors can influence peripheral immune macroenvironment, thereby creating opportunities for non-invasive serum/plasma immunobiomarkers for immunostratification and immunotherapy designing. However, current approaches for immunobiomarkers’ detection are largely quantitative, which is unreliable for assessing functional peripheral immunodynamics of patients with cancer. Hence, we aimed to design a functional biomarker modality for capturing peripheral immune signaling in patients with cancer for reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…Due to the high level of malignancy and poor prognosis of glioma (Xun et al, 2021), the development of accurate methods is required to predict the associated prognosis and to create effective therapy for patients with glioma. At present, immunotherapy demonstrates high levels of effectiveness in the treatment of malignant tumors (Chen et al, 2021b;Sprooten et al, 2021). Results of previous studies have demonstrated that TIME exhibits a high association with the occurrence and development of several tumor types, and this may act as an important prognostic indicator (Berraondo et al, 2016;Elola et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high level of malignancy and poor prognosis of glioma (Xun et al, 2021), the development of accurate methods is required to predict the associated prognosis and to create effective therapy for patients with glioma. At present, immunotherapy demonstrates high levels of effectiveness in the treatment of malignant tumors (Chen et al, 2021b;Sprooten et al, 2021). Results of previous studies have demonstrated that TIME exhibits a high association with the occurrence and development of several tumor types, and this may act as an important prognostic indicator (Berraondo et al, 2016;Elola et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Both type I and type II IFNs can elicit the transcription of ISGs, which include the IFN-inducible CXCL9/CXCL10/CXCL11 chemokines. In the current study, we investigated whether the “sum total” of circulating proteins can result in the activation of IFN/ISG response within myeloid cells via newly established sFIS assay [ 36 ]. In patients with stage I NSCLC treated with SBRT, increased IFN/ISG response activity was associated with a better PFS.…”
Section: Discussionmentioning
confidence: 99%
“…This sFIS assay [ 36 ] consisted of THP1-Dual™ myeloid reporter cells (InvivoGen, Toulouse, France) seeded in a 96-well plate at a density of 30,000 cells per well in 100 µL media (RPMI-1640 containing 2 mM L-glutamine, 25 mM HEPES, 100 units/mL penicillin, 100 µg/L streptomycin, 100 µg/mL Normocin and 10% heat inactivated fetal calf serum). After 24 h, THP1 cells were treated with 100 µL of patient plasma for 24 h. To determine activation of interferon-stimulated response elements (ISRE) coding for interferon (IFN)-stimulated genes (ISG), luciferase was checked in media by adding 50 µL of Quanti-Luc GOLD (InvivoGen) to 100 µL of (separately recovered) THP1 media.…”
Section: Methodsmentioning
confidence: 99%
“…Although tumor sampling is widely implemented for biomarker identification and analysis, there are several challenges including limited accessibility, heterogeneity of the biopsy site, and the patient’s condition. 11 Therefore, identification of potential predictive biomarkers using more accessible peripheral blood is critical for the development and clinical utility of biomarkers. 12 , 13 Recent technological, analytical, and mechanistic advances in immunology have enabled the identification of several circulating cancer biomarkers including, but not limited to: circulating tumor cells in breast and prostate cancer, tumor genomic alterations such as discrete oncogenic variants (e.g.…”
Section: Introductionmentioning
confidence: 99%